A case series of Brugada syndrome with a novel mutation in the ankyrin-B gene: an unusual unmasking in acute myocarditis. Issue 6 (30th June 2021) - Marketou, Maria E; Zareas, Ilias; Kanoupakis, Emmanuel; Patrianakos, Alexandros; Parthenakis, Fragiskos
Abstract: Background : Brugada syndrome (BrS) is a genetically heterogeneous channelopathy that may lead to sudden death. We report a novel mutation of the ankyrin-B gene that is probably related to the occurrence of BrS in two brothers. Case summary : First, we present the case of a 27-year-old male who was admitted to the hospital with acute myocarditis. The patient showed left ventricular dysfunction and was given carvedilol. Six days later, while asymptomatic and afebrile, the patient exhibited an electrocardiogram (ECG) with repolarization 'saddleback' ST changes in V2. A procainamide provocative test was performed with a response for Type 1 Brugada ECG pattern. Genetic testing revealed a novel mutation, c.5418T>A (+/−) (p.His1806Gln), in the ankyrin-B gene encoding. His 34 years old brother had an ECG J point elevation in leads V1 and V2 of 1 mm not fulfilling diagnostic criteria for Brugada ECG pattern. He also experienced arrhythmia-related syncope. Flecainide provocation test changed ECG towards a Type 1 Brugada pattern. A subcutaneous implantable defibrillator (ICD) was implanted. Patient 1 remains asymptomatic while Patient 2 experienced an appropriate ICD shock during follow-up. Discussion : In this case series, two brothers with BrS exhibited the same mutation of the ankyrin-B gene. Ankyrin-B is associated with the stability of plasma membrane proteins in the voltage-gated ion channels. Our finding provides a foundation for further investigation of this mutation in relation to BrS. Moreover, the timing of its presentation raises concerns as to whether myocarditis or beta-blockers are associated with the presentation of BrS ECG.